Lithium ion battery negative electrode with long cycle life and high initial efficiency and preparation method thereof

By adopting a composite fluid-collection structure and lithium-enhancing coating on the negative electrode of the lithium-ion battery, combined with ceramicized silicone foam and modified thermally conductive silicone, the low efficiency and insufficient cycle stability of the lithium-ion battery anode material during the first lithium embedding process is solved. The problem has significantly improved the energy density and safety performance of the battery.

CN119324201APending Publication Date: 2025-01-17广东嘉尚新能源材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411357906.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing lithium-ion battery anode materials have low efficiency, insufficient cycle stability and uneven stress distribution during the first lithium embedding process, resulting in insufficient energy density, cycle life and safety performance.

Method used

Using a composite liquid collecting structure, coated with silicon carbon negative electrode active material and lithium supplement coating, including inorganic lithium-containing compounds, Elosite nanotube powder and lithium polyacrylate, combined with ceramicized silicone foam and modified thermally conductive silicone to form mutual Lock structure to improve the stability and safety of the electrodes.

Benefits of technology

The first discharge efficiency, cycle life and safety performance of lithium-ion batteries are improved, and lithium dendrites are prevented from being generated and short-circuited internally by slowing release of lithium ions and enhancing electrode stability and mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119324201A_ABST
    Figure CN119324201A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium ion battery negative electrode with long cycle life and high first efficiency and a preparation method thereof. The lithium ion battery negative electrode comprises a composite current collector, a silicon-carbon negative electrode active material coating coated on at least one surface of the composite current collector, and a lithium supplementing coating coated on the outer surface of the silicon-carbon negative electrode active material coating, the lithium supplementing coating comprises an inorganic lithium-containing compound, halloysite nanotube powder and lithium polyacrylate, and the mass part ratio of the inorganic lithium-containing compound to the halloysite nanotube powder to the lithium polyacrylate is (20-25): (65-75): (2-5); the inorganic lithium-containing compound is a mixture formed by lithium borate and lithium carbonate according to the mass ratio of (1-2): 1. Compared with the prior art, the lithium ion battery negative electrode provided by the invention has relatively high first efficiency, relatively long cycle life and relatively high safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery negative electrode with long cycle life and high initial efficiency and a preparation method thereof. Background Art

[0002] Since the commercialization of lithium-ion batteries in the 1990s, they have been widely used in portable electronic devices, power tools, new energy vehicles and other fields due to their advantages such as high energy density, long cycle life and no memory effect. However, with the development of society and the advancement of science and technology, people have put forward higher requirements for the energy density, cycle life and safety performance of lithium-ion batteries. As a key component of lithium-ion batteries, the performance of negative electrode materials has a decisive influence on the overall performance of batteries.

[0003] Traditional lithium-ion battery negative electrode materials mainly use graphite, but the theoretical specific capacity of graphite is only 372mAh / g, which can no longer meet the growing demand for high energy density. In order to further improve the specific capacity of the negative electrode, silicon-based materials have attracted widespread attention due to their theoretical specific capacity of up to 4200mAh / g. However, the volume expansion of silicon during the lithium insertion process is as high as 300%, resulting in problems such as pulverization of active materials, destruction of electrode structure, and intensification of interface side reactions, which seriously affects the cycle stability and safety performance of silicon-based negative electrodes.

[0004] In order to overcome the above defects of silicon-based negative electrodes, researchers have proposed a variety of modification strategies, such as using nanostructured silicon materials, constructing silicon-carbon composite materials, introducing coating layers, etc. Among them, silicon-carbon composite materials have become one of the most promising negative electrode materials because they have both the high specific capacity of silicon and the good conductivity and structural stability of carbon. However, existing silicon-carbon composite materials still face the following challenges in practical applications:

[0005] 1) Low initial coulombic efficiency: During the initial lithium insertion process of silicon-carbon composite materials, the formation of solid electrolyte interface film (SEI film) is inevitable, which consumes a large amount of lithium ions and causes serious first irreversible capacity loss, thus reducing the energy density and commercial prospects of the battery.

[0006] 2) Insufficient cycle stability: During the long-term cycle of silicon-carbon composite materials, the volume expansion and contraction of silicon particles will lead to poor contact between the active material and the current collector, aggravate electrochemical polarization, cause problems such as active material shedding and electrolyte decomposition, and seriously affect the cycle life of the electrode.

[0007] 3) Uneven stress distribution, easy to produce lithium dendrites: During the lithium embedding process of silicon-carbon composite materials, the volume expansion of silicon particles is much greater than that of the carbon matrix, resulting in uneven stress distribution inside the electrode. The stress concentration area is easy to become the growth point of lithium dendrites, causing lithium dendrites to pierce the diaphragm, causing internal short circuit of the battery, and seriously threatening the safety performance of the battery.

[0008] Therefore, there is an urgent need to develop a lithium-ion battery negative electrode with a long cycle life and high initial efficiency, so as to comprehensively improve the initial efficiency, cycle life and safety of the lithium-ion battery negative electrode. Summary of the invention

[0009] The main purpose of the present invention is to provide a lithium-ion battery negative electrode with a long cycle life and high initial efficiency in view of the deficiencies in the prior art, so as to comprehensively improve the initial efficiency, cycle life and safety performance of the lithium-ion battery negative electrode.

[0010] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0011] A lithium-ion battery negative electrode with long cycle life and high first efficiency comprises a composite current collector, a silicon-carbon negative electrode active material coating coated on at least one surface of the composite current collector, and a lithium-supplementing coating coated on the outer surface of the silicon-carbon negative electrode active material coating; the lithium-supplementing coating comprises an inorganic lithium-containing compound, halloysite nanotube powder and lithium polyacrylate, the mass fraction ratio of the inorganic lithium-containing compound, the halloysite nanotube powder and the lithium polyacrylate is (20-25): (65-75): (2-5); the inorganic lithium-containing compound is a mixture of lithium borate and lithium carbonate in a mass ratio of (1-2):1.

[0012] Preferably, the particle size of the inorganic lithium-containing compound is R1, and the particle size of the halloysite nanotube powder is R2, wherein R1 and R2 satisfy the relationship: 2≤R1 / R2≤5.

[0013] Preferably, the particle size R1 of the inorganic lithium-containing compound is 2-50 μm, and the particle size R2 of the halloysite nanotube powder is 1-10 μm.

[0014] Preferably, the thickness of the lithium replenishing coating is 1-5 μm.

[0015] Preferably, the silicon-carbon negative electrode active material coating comprises a silicon-carbon material, a conductive agent and a binder, and the mass ratio of the silicon-carbon material, the conductive agent and the binder is (80~99.5):(0.2~10):(0.3~10); the silicon-carbon material is a mixture of silicon oxide and hard carbon in a mass ratio of 1:(1~2), the conductive agent is at least one of carbon nanofibers, carbon nanotubes and graphene, and the binder is at least one of lithium polyacrylate, ethylene oxide, nitrile rubber, styrene-butadiene rubber and polyvinyl alcohol.

[0016] Preferably, the composite current collector includes a first copper foil layer, a second copper foil layer, and a heat-resistant buffer material layer arranged between the first copper foil layer and the second copper foil layer; a plurality of trapezoidal protrusions are arranged on both side surfaces of the heat-resistant buffer material layer, and the first copper foil layer and the second copper foil layer are both provided with a plurality of trapezoidal grooves embedded with the trapezoidal protrusions, the cross-sectional width of the trapezoidal protrusions gradually increases from the inside to the outside, and the cross-sectional width of the trapezoidal grooves gradually decreases from the inside to the outside, and an interlocking structure is formed between the first copper foil layer and the second copper foil layer through the cooperation of the trapezoidal protrusions and the trapezoidal grooves.

[0017] Preferably, the heat-resistant buffer material layer is a ceramic silicone foam, which includes the following components in weight proportions: 30 to 40 parts of vinyl silicone oil, 10 to 20 parts of white carbon black, 20 to 50 parts of nano-ceramic powder, 0.1 to 1.0 parts of ethynyl cyclohexanol, 1 to 10 parts of hydrogen-containing silicone oil, 1 to 10 parts of hydroxyl silicone oil, 0.1 to 1.0 parts of platinum catalyst, 10 to 20 parts of β-eucryptite, and 1 to 8 parts of halloysite nanotubes.

[0018] Preferably, the height of the trapezoidal protrusion is g, the depth of the trapezoidal groove is h, the cross-sectional width of the trapezoidal protrusion is w, the cross-sectional width of the trapezoidal groove is d, the thickness of the heat-resistant buffer material layer is G, and the thickness of the first copper foil layer and the second copper foil layer are both H, wherein g, h, w, d, G and H satisfy the relationship: g=h, w=d, 0.1G≤g≤0.3G, 0.2H≤h≤0.4H, H<G.

[0019] Preferably, the sum of the forward projection areas of all trapezoidal protrusions on the surface of one side of the heat-resistant buffer material layer is S1, and the forward projection area of ​​the heat-resistant buffer material layer is S; wherein S1 and S satisfy the relationship: 0.5S≤S1≤0.7S.

[0020] Preferably, the preparation method of the ceramic silica foam is as follows:

[0021] Step S1, adding vinyl silicone oil, white carbon black, nano ceramic powder and β-eucryptite into a kneader, kneading into a mass at 130-150° C., cooling, and obtaining a base rubber;

[0022] Step S2, stirring and mixing the hydroxy silicone oil and the halloysite nanotubes to obtain a foaming mixture; wherein the stirring and mixing speed is 23000-26000 r / min, and the mixing time is 10-25 s;

[0023] Step S3, adding the foaming mixture, ethynyl cyclohexanol, hydrogen-containing silicone oil, and platinum catalyst into the base rubber, mixing evenly, to obtain a rubber material;

[0024] Step S4, vulcanizing and foaming the rubber material by a molding process to obtain the ceramicized silicone foam.

[0025] Preferably, one or more pressure sensors are embedded in the heat-resistant buffer material layer to monitor the pressure borne by various regions of the negative electrode in real time.

[0026] Preferably, a first temperature control material layer is provided between the first copper foil layer and the heat-resistant buffer material layer, and a second temperature control material layer is provided between the second copper foil layer and the heat-resistant buffer material layer; the shapes of the first temperature control material layer and the second temperature control material layer are both adapted to the shape of the trapezoidal raised surface of the heat-resistant buffer material layer; the phase change temperatures of the first temperature control material layer and the second temperature control material layer are both 57~62°C.

[0027] Preferably, the first temperature control material layer and the second temperature control material layer both include the following compositions in weight proportions: 45-55 parts of octadecanoic acid glycerol, 20-25 parts of palmitic acid, 10-15 parts of polyethylene glycol 4000, 3-5 parts of carbon nanotubes, 2-3 parts of boron nitride nanosheets, 1-2 parts of expanded graphite, and 0.5-1 parts of nano-magnesium oxide.

[0028] Preferably, the preparation method of the first temperature control material layer or the second temperature control material layer is as follows:

[0029] (1) Stearyl glycerol and palmitic acid are mixed according to a ratio, heated to melt in an oil bath at 85-95° C., and stirred evenly;

[0030] (2) adding polyethylene glycol 4000 to the molten mixture of step (1) and continuing to stir until it is completely dissolved;

[0031] (3) dispersing carbon nanotubes and boron nitride nanosheets in N-methylpyrrolidone and ultrasonically treating for 30 minutes;

[0032] (4) slowly adding the suspension of step (3) into the molten mixture of step (2), and stirring at high speed for 45 minutes;

[0033] (5) adding expanded graphite and nano magnesium oxide, and continuing high-speed stirring for 20 minutes to obtain a temperature control material layer slurry;

[0034] (6) Spraying the temperature control material layer slurry onto the outer surface of the heat-resistant buffer material layer and drying it to obtain a first temperature control material layer or a second temperature control material layer of a desired shape and thickness.

[0035] Preferably, a first modified thermally conductive silicone is further arranged between the first copper foil layer and the heat-resistant buffer material layer, and a second modified thermally conductive silicone is further arranged between the second copper foil layer and the heat-resistant buffer material layer; the shapes of the first modified thermally conductive silicone and the second modified thermally conductive silicone are both adapted to the shape of the trapezoidal raised surface of the heat-resistant buffer material layer; the porosity of the first modified thermally conductive silicone and the second modified thermally conductive silicone are both 65%~85%; the first copper foil layer and the heat-resistant buffer material layer are bonded and connected by the first modified thermally conductive silicone; the second copper foil layer and the heat-resistant buffer material layer are bonded and connected by the second modified thermally conductive silicone.

[0036] In addition, the present invention also provides a method for preparing a negative electrode of a lithium ion battery with a long cycle life and high initial efficiency, comprising the following steps:

[0037] 1) Composite current collector production:

[0038] a) preparing a ceramic silicone foam rubber material according to the above-mentioned method for preparing the ceramic silicone foam;

[0039] b) vulcanizing and foaming the ceramic silicone foam rubber material through a molding process to obtain a heat-resistant buffer material layer having trapezoidal protrusions on both sides of the surface;

[0040] c) spraying a copper foil layer of the same thickness on the surface of the heat-resistant buffer material layer by magnetron sputtering, and drying the copper foil layer to obtain a composite current collector;

[0041] 2) Preparation of silicon-carbon negative electrode active material coating:

[0042] d) mixing the silicon-carbon material, the conductive agent and the binder in a mass ratio of (80-99.5):(0.2-10):(0.3-10) in deionized water, and stirring evenly to obtain a silicon-carbon negative electrode active material coating slurry;

[0043] e) coating the negative electrode active material coating slurry on at least one surface of the composite current collector and drying it to obtain a silicon-carbon negative electrode active material coating;

[0044] 3) Preparation of lithium supplement coating:

[0045] f) mixing an inorganic lithium-containing compound, halloysite nanotube powder and lithium polyacrylate in a mass ratio of (20-25):(65-75):(2-5) in deionized water to make a solid content of 50-60%, thereby obtaining a lithium supplement coating slurry;

[0046] g) coating the lithium supplement coating slurry on the outer surface of the silicon-carbon negative electrode active material coating and drying the coating to obtain a lithium ion battery negative electrode containing the lithium supplement coating.

[0047] Compared with the prior art, the present invention has at least the following beneficial effects:

[0048] 1) The present invention coats a lithium-supplementing coating with a sustained-release effect on the outer surface of the silicon-carbon negative electrode active material coating of the negative electrode, and the lithium-supplementing coating includes an inorganic lithium-containing compound, halloysite nanotube powder and lithium polyacrylate; wherein the inorganic lithium-containing compound provides an additional lithium source to supplement the loss of lithium ions during the first charge and discharge process and improve the first discharge efficiency; the high specific surface area and good adsorption characteristics of the halloysite nanotube powder can effectively release lithium ions and enhance the stability and durability of the electrode; lithium polyacrylate is used as a binder to enhance the adhesion between materials and ensure the integrity and stability of the lithium-supplementing coating; specifically, By adsorbing inorganic lithium-containing compounds on halloysite nanotube powder, a stable lithium source is provided for the battery during use. During the first charge and discharge process, since some inorganic lithium-containing compounds are embedded in the tubular structure of halloysite nanotubes during the pulping process, the embedded part dissolves relatively slowly during the reaction and will gradually dissolve in the electrolyte to release lithium ions, replenishing the lithium ions consumed when the SEI film is formed, thereby improving the initial efficiency of the battery; at the same time, the SEI film on the surface of the negative electrode is quickly formed and reaches a stable state, thereby improving the quality of the SEI film, maintaining the concentration of lithium salt in the electrolyte, and improving the cycle life of the battery.

[0049] 2) The inorganic lithium-containing compound of the present invention is a mixture of lithium borate and lithium carbonate in a mass ratio of (1~2):1. Among them, lithium carbonate can be rapidly decomposed to generate lithium ions during the initial charge and discharge process of the battery, thereby providing additional lithium compensation. The decomposition of lithium carbonate also helps to form a stable SEI film, which is beneficial to improve the first efficiency of the battery; during the charge and discharge process, the borate anions of lithium borate can reversibly deintercalate with lithium ions to form a stable boron oxygen six-membered ring structure, which improves the migration rate and reversibility of lithium ions, and lithium borate has excellent thermal stability and chemical stability, which can inhibit the decomposition and side reactions of the electrolyte and improve the safety and cycle life of the battery. Therefore, the inorganic lithium-containing compound of the present invention uses lithium borate and lithium carbonate to mix, which has the following advantages: first, lithium borate provides a high content of lithium source and excellent lithium ion reversibility, while lithium carbonate provides a stable and reliable lithium source and good interface compatibility. The synergistic effect of the two can effectively compensate for the irreversible capacity loss of the silicon-carbon negative electrode in the first cycle and improve the first coulomb efficiency. Secondly, after lithium borate and lithium carbonate are mixed, a more stable boron-oxygen coordination network structure and carbonate interface layer can be formed, which can improve the mechanical strength and chemical stability of the lithium-replenishing coating and prevent peeling or decomposition during long-term cycles. In addition, the mixture of lithium borate and lithium carbonate has a moderate solubility in the electrolyte, which can maintain the integrity of the lithium-replenishing coating, while ensuring the gradual release and uniform distribution of lithium ions, avoiding side reactions or interface passivation caused by local excessive release. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 is a schematic cross-sectional structure diagram of a negative electrode in one embodiment of the present invention;

[0051] Figure 2 Schematic diagram of the structure of a composite current collector of a negative electrode in one embodiment of the present invention;

[0052] Figure 3 is a structural exploded view of a composite current collector of a negative electrode in one embodiment of the present invention;

[0053] Figure 4 is a schematic cross-sectional structure diagram of a negative electrode in another embodiment of the present invention;

[0054] Figure 5 is a structural exploded view of a composite current collector of a negative electrode in another embodiment of the present invention;

[0055] Figure 6 FIG. 4 is a structural exploded view of a composite current collector of a negative electrode in another embodiment of the present invention.

[0056] In the figure: 1. composite current collector; 11. first copper foil layer; 12. second copper foil layer; 13. heat-resistant buffer material layer; 14. trapezoidal protrusion; 15. trapezoidal groove; 16. first temperature control material layer; 17. second temperature control material layer; 18. first modified thermally conductive silica gel; 19. second modified thermally conductive silica gel; 2. negative electrode active material coating; 3. lithium supplement coating; 4. pressure sensor. DETAILED DESCRIPTION

[0057] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0058] Please refer to the attached Figures 1 to 3 The present embodiment provides a lithium-ion battery negative electrode with a long cycle life and high first efficiency, comprising a composite current collector 1, a silicon-carbon negative electrode active material coating 2 coated on at least one surface of the composite current collector 1, and a lithium supplement coating 3 coated on the outer surface of the silicon-carbon negative electrode active material coating 2; the lithium supplement coating 3 comprises an inorganic lithium-containing compound, halloysite nanotube powder and lithium polyacrylate, and the mass ratio of the inorganic lithium-containing compound, halloysite nanotube powder and lithium polyacrylate is (20~25):(65~75):(2~5); the inorganic lithium-containing compound is combined into a mixture of lithium borate and lithium carbonate in a mass ratio of (1~2):1.

[0059] The lithium supplement coating 3 includes an inorganic lithium-containing compound, halloysite nanotube powder and lithium polyacrylate; wherein the inorganic lithium-containing compound provides an additional lithium source to supplement the loss of lithium ions during the first charge and discharge process and improve the first discharge efficiency; the high specific surface area and good adsorption characteristics of the halloysite nanotube powder can effectively release lithium ions and enhance the stability and durability of the electrode; lithium polyacrylate is used as a binder to enhance the adhesion between materials and ensure the integrity and stability of the lithium supplement coating 3. During the first charge and discharge process, since part of the inorganic lithium-containing compound is embedded in the tubular structure of the halloysite nanotube during the pulping process, the embedded part dissolves relatively slowly during the reaction process and will gradually dissolve in the electrolyte to release lithium ions, supplementing the consumption of lithium ions during the formation of the SEI film and improving the first efficiency of the battery; at the same time, the SEI film on the surface of the negative electrode is quickly formed and reaches a stable state, which improves the quality of the SEI film, maintains the concentration of lithium salt in the electrolyte, and improves the cycle life of the battery.

[0060] Among them, compared with conventional single inorganic lithium-containing compounds (such as Li2CO3), the mixture of lithium borate and lithium carbonate used in the present invention has the following advantages: 1) The high lithium content and excellent lithium ion reversibility of lithium borate can make up for the relatively low lithium content of lithium carbonate and provide more sufficient and efficient lithium compensation. 2) The mixture of lithium borate and lithium carbonate has a moderate solubility in the electrolyte, which can achieve progressive lithium release and uniform distribution, avoiding local unevenness or side reactions caused by low or high solubility of a single lithium-containing compound. 3) The boron-oxygen coordination network structure formed by lithium borate and the carbonate interface layer formed by lithium carbonate can synergistically improve the stability and compatibility of the lithium-replenishing coating 3 and the silicon-carbon negative electrode interface, and promote lithium ion transfer kinetics, while a single lithium-containing compound is difficult to take into account both aspects. 4) The mixture of lithium borate and lithium carbonate has more excellent thermal stability and chemical stability, which can improve the safety performance of the battery under high temperature or overcharge conditions, while the stability of a single lithium-containing compound may have certain limitations.

[0061] Therefore, using a mixture of lithium borate and lithium carbonate as an inorganic lithium-containing compound can give play to the synergistic effect of the two, provide efficient and reversible lithium compensation, improve the first coulombic efficiency and cycle stability of the silicon-carbon negative electrode, while taking into account the lithium ion transfer kinetics, interface compatibility and safety performance, which has significant advantages over conventional single inorganic lithium-containing compounds.

[0062] In one implementation of the present application, the particle size of the inorganic lithium-containing compound is R1, and the particle size of the halloysite nanotube powder is R2, wherein R1 and R2 satisfy the relationship: 2≤R1 / R2≤5. This particle size ratio can ensure that the inorganic lithium-containing compound is fully adsorbed and embedded in the halloysite nanotube powder, achieve a controllable lithium ion release and compensation process, maintain the stability and integrity of the SEI film, and improve the first efficiency and cycle life of the battery. If the particle size of the halloysite nanotube powder is too small, the amount of inorganic lithium-containing compound embedded is small; if the particle size of the halloysite nanotube powder is too large, it cannot be fully embedded and wastes space.

[0063] In one implementation of the present application, the particle size R1 of the inorganic lithium-containing compound is 2 to 50 μm, and the particle size R2 of the halloysite nanotube powder is 1 to 10 μm. Among them, controlling the particle size of the inorganic lithium-containing compound within this range can provide an appropriate dissolution rate, gradually release lithium ions in the first cycle, compensate for the lithium loss formed by the SEI film, and improve the first coulomb efficiency. Controlling the particle size of the halloysite nanotube powder within this range can provide a high specific surface area and excellent adsorption performance, adsorb and fix the inorganic lithium-containing compound, form a uniform and stable composite structure, and improve the lithium loading and mechanical strength of the lithium supplement coating 3.

[0064] In one implementation of the present application, the thickness of the lithium replenishing coating 3 is 1-5 μm.

[0065] In one implementation of the present application, the lithium replenishing coating 3 also includes an amine-based stabilizer in an amount of 1 to 5 parts by weight, and the amine-based stabilizer is BASF Tinuvin 144 or BASF Tinuvin 770. The present invention can effectively alleviate the problem of battery performance degradation under high-voltage working conditions by introducing an amine-based stabilizer into the lithium replenishing coating 3. Specifically, under high-voltage conditions, active oxygen or oxygen will be released during the delithiation process of inorganic lithium-containing compounds and positive electrode active materials, which will damage the electrolyte solvent. Therefore, the present application adds an amine-based stabilizer into the lithium replenishing coating 3, and its amine-based functional group can react with oxygen free radicals to block the damage of oxygen free radicals to the electrolyte solvent, thereby effectively improving the cycle performance of the battery and further improving the cycle life of the battery.

[0066] In one implementation of the present application, the silicon-carbon negative electrode active material coating 2 includes a silicon-carbon material, a conductive agent and a binder, and the mass ratio of the silicon-carbon material, the conductive agent and the binder is (80~99.5):(0.2~10):(0.3~10); the silicon-carbon material is a mixture of silicon oxide and hard carbon in a mass ratio of 1:(1~2), the conductive agent is at least one of carbon nanofibers, carbon nanotubes and graphene, and the binder is at least one of lithium polyacrylate, ethylene oxide, nitrile rubber, styrene-butadiene rubber and polyvinyl alcohol.

[0067] In one implementation of the present application, the composite current collector 1 includes a first copper foil layer 11, a second copper foil layer 12, and a heat-resistant buffer material layer 13 arranged between the first copper foil layer 11 and the second copper foil layer 12; a plurality of trapezoidal protrusions 14 are arranged on both side surfaces of the heat-resistant buffer material layer 13, and the first copper foil layer 11 and the second copper foil layer 12 are both provided with a plurality of trapezoidal grooves 15 embedded with the trapezoidal protrusions 14, the cross-sectional width of the trapezoidal protrusions 14 gradually increases from the inside to the outside, and the cross-sectional width of the trapezoidal grooves 15 gradually decreases from the inside to the outside, and an interlocking structure is formed between the first copper foil layer 11 and the second copper foil layer 12 through the cooperation of the trapezoidal protrusions 14 and the trapezoidal grooves 15.

[0068] The present invention adopts a composite current collector 1 structure including a first copper foil layer 11, a second copper foil layer 12 and a heat-resistant buffer material layer 13 arranged between the two copper foil layers, wherein the heat-resistant buffer material layer 13 selects ceramic silicone foam of specific components and proportions; the material design gives the composite current collector 1 excellent high temperature resistance, flame retardancy and mechanical buffering performance; under high temperature thermal runaway conditions, the ceramic silicone foam can maintain good mechanical strength and structural integrity, play a role in heat insulation and flame retardancy, effectively delay the occurrence and spread of thermal runaway, and greatly improve the thermal stability and safety of the negative electrode. The present invention designs an interlocking structure in which a trapezoidal protrusion 14 and a trapezoidal groove 15 are embedded between the heat-resistant buffer material layer 13 and the copper foil layer; this structure greatly increases the interface contact area and mechanical bite force, and significantly improves the interface bonding strength and shear resistance; the interlocking structure can effectively resist the interface shear stress, prevent interface delamination or peeling, ensure the interface connection reliability and conductivity stability of the composite current collector 1 in long-term charge and discharge cycles, and improve the cycle life and mechanical fatigue performance of the negative electrode. In addition, the porous buffer structure of the ceramic silicone foam, combined with the interlocking design of protrusions and grooves, gives the composite current collector 1 excellent buffering energy absorption and pressure equalization properties; the negative electrode can effectively absorb and dissipate internal or external impact and vibration energy, protect the battery from mechanical stress damage, and absorb the negative electrode expansion force, reduce the volume change of the negative electrode material, maintain the relative stability of the negative electrode structure, inhibit the generation of negative electrode lithium dendrites, and thereby reduce the risk of internal short circuits in the battery, ensuring the safety and reliability of the battery; at the same time, the interlocking structure makes the stress distribution inside the negative electrode more uniform, reduces the risk of local deformation or damage caused by stress concentration, and greatly improves the battery's vibration and impact resistance and mechanical stability.

[0069] In one implementation of the present application, the heat-resistant buffer material layer 13 is a ceramic silicone foam, which includes the following components in weight proportions: 30 to 40 parts of vinyl silicone oil, 10 to 20 parts of white carbon black, 20 to 50 parts of nano-ceramic powder, 0.1 to 1.0 parts of ethynyl cyclohexanol, 1 to 10 parts of hydrogen-containing silicone oil, 1 to 10 parts of hydroxyl silicone oil, 0.1 to 1.0 parts of platinum catalyst, 10 to 20 parts of β-eucryptite, and 1 to 8 parts of halloysite nanotubes.

[0070] The ceramic silicone foam provided by the present invention not only has good elasticity under normal working conditions, but also can play a good buffering role for the composite current collector 1; and at high temperatures, the ceramic silicone foam can quickly form a foam ceramic body with a self-supporting structure, and can maintain a high degree of pore structure retention rate, thereby exerting excellent heat insulation and flame retardant effects, and it can withstand the burning of flames above 1300°C for a long time, can effectively block the transfer of fire and temperature, effectively inhibit the combustion reaction inside the battery, and hinder the spread and propagation of flames. For example, when the temperature inside the battery rises abnormally, the ceramic silicone foam plays a role in heat insulation and insulation, delays the accumulation and transfer of heat, buys precious time for the activation of battery safety protection measures, and effectively prevents or delays the occurrence of thermal runaway accidents; when the battery has abnormal conditions such as internal short circuit, overcharge, over discharge, etc., the ceramic silicone foam can prevent the chain reaction caused by the combustion of the electrolyte and reduce the risk of battery fire or explosion.

[0071] Among them, vinyl silicone oil is the main polymer matrix, which provides the required elasticity and flexibility in the foaming system; it can form a cross-linked structure by reacting with hydrogen-containing silicone oil, thereby enhancing the mechanical strength of the material. Silica is used as a reinforcing agent. Silica increases the tear strength and wear resistance of the composite material, while improving the compression resistance of silicone rubber, making the material less likely to deform even under higher loads. Nano-ceramic powder acts as a flame retardant. At high temperatures, nano-ceramic powder can promote the formation of a hard ceramic layer on the surface of the material, effectively preventing the further spread of flames and heat. Ethylene cyclohexanol is used as an inhibitor. This compound can control the rate of polymerization and avoid structural instability caused by too fast a reaction. Hydrogen-containing silicone oil acts as a cross-linking agent and reacts with vinyl silicone oil to form a silicone rubber network structure, enhancing the overall mechanical properties and thermal stability of the material. Hydroxyl silicone oil acts as a foaming agent in this system. Hydroxyl silicone oil decomposes and produces gas when heated to form a foam structure, thereby providing good cushioning properties and low density. Platinum catalyst catalyzes the addition cross-linking reaction of vinyl silicone oil and hydrogen silicone oil, improving the efficiency and uniformity of the reaction and ensuring the consistency of material performance. β-eucryptite, as a ceramic-forming agent, can promote the transformation of silicone rubber into ceramic body at high temperature, enhancing the high temperature resistance and structural stability of the material. Halloysite nanotubes, as a pore structure stabilizer, can form a uniformly distributed support structure in the material, enhance the stability of the pore structure, and avoid collapse under high temperature or mechanical pressure.

[0072] Therefore, through these specific components and their synergistic effects, the ceramicized silicone foam of the present invention not only maintains excellent elasticity and flexibility, but also significantly improves the performance of the material under extreme conditions. Moreover, at high temperatures, the material can quickly form a self-supporting foam ceramic body, greatly improving the heat insulation and flame retardancy. This foam ceramic body can maintain its structural integrity and flame retardancy when subjected to high temperatures or direct flame irradiation, unlike traditional silicone foams that may crack, deform, collapse or even pulverize under the same conditions, thereby losing its protective ability.

[0073] In one implementation of the present application, the height of the trapezoidal protrusion 14 is g, the depth of the trapezoidal groove 15 is h, the cross-sectional width of the trapezoidal protrusion 14 is w, the cross-sectional width of the trapezoidal groove 15 is d, the thickness of the heat-resistant buffer material layer 13 is G, and the thickness of the first copper foil layer 11 and the second copper foil layer 12 are both H, wherein g, h, w, d, G and H satisfy the relationship: g=h, w=d, 0.1G≤g≤0.3G, 0.2H≤h≤0.4H, H<G. When the above relationship is satisfied between the protrusion height, the groove depth, the protrusion width, the groove width, and the heat-resistant buffer layer and the copper foil layer thickness, it is possible to ensure sufficient mechanical interlocking strength and buffering performance while taking into account the lightweight and thin design of the composite current collector 1, and while improving the mechanical reliability of the negative electrode, the volume and weight of the negative electrode are reduced, thereby improving the energy density of the battery.

[0074] In one implementation of the present application, the height g of the trapezoidal protrusion 14 is 1.6~6.4μm, the depth h of the trapezoidal groove 15 is 1.6~6.4μm, the cross-sectional width w of the trapezoidal protrusion 14 is 50~500μm, the cross-sectional width d of the trapezoidal groove 15 is 50~500μm, the thickness G of the heat-resistant buffer material layer 13 is 16~21.4μm, and the thickness H of the first copper foil layer 11 and the second copper foil layer 12 are both 8~16μm.

[0075] In one implementation of the present application, the sum of the forward projection areas of all the trapezoidal protrusions 14 on one side of the heat-resistant buffer material layer 13 is S1, and the forward projection area of ​​the heat-resistant buffer material layer 13 is S; wherein S1 and S satisfy the relationship: 0.5S≤S1≤0.7S. This can provide a sufficiently large interlocking contact area to ensure the reliability of the interface bonding, and can also avoid the excessively large projection area that leads to insufficient buffer deformation space of the heat-resistant buffer layer, while ensuring the interlocking strength and maintaining the good buffering energy absorption performance of the composite current collector 1.

[0076] In one implementation of the present application, the preparation method of the ceramic silicone foam is as follows:

[0077] Step S1, adding vinyl silicone oil, white carbon black, nano ceramic powder and β-eucryptite into a kneader, kneading into a mass at 130-150° C., cooling, and obtaining a base rubber;

[0078] Step S2, stirring and mixing the hydroxy silicone oil and the halloysite nanotubes to obtain a foaming mixture; wherein the stirring and mixing speed is 23000-26000 r / min, and the mixing time is 10-25 s;

[0079] Step S3, adding the foaming mixture, ethynyl cyclohexanol, hydrogen-containing silicone oil, and platinum catalyst into the base rubber, mixing evenly, to obtain a rubber material;

[0080] Step S4, vulcanizing and foaming the rubber material by a molding process to obtain ceramic silicone foam.

[0081] Among them, the ceramic silicone foam prepared in this application has the following advantages:

[0082] 1) Excellent mechanical properties and elasticity: Due to the cross-linked structure of vinyl silicone oil and hydrogen silicone oil, plus the reinforcement effect of white carbon black, the silicone foam of the present invention has good elasticity and resistance to mechanical stress, so that it can maintain its original shape and function after long-term use or repeated compression.

[0083] 2) Highly efficient flame retardant and heat insulation capabilities: The addition of nano-ceramic powder and β-eucryptite enables the material to quickly form a protective ceramic layer when exposed to high temperature or flame. This layer of structure can not only effectively isolate the flame, but also reduce heat transfer and protect the internal structure from damage.

[0084] 3) Highly stable foam structure: The gas generated by the decomposition of hydroxy silicone oil forms a foam structure, and its stability is enhanced by halloysite nanotubes, making the foam less likely to collapse even at high temperatures and maintaining a high pore structure retention rate.

[0085] 4) Excellent heat resistance: The controlled polymerization rate of ethynyl cyclohexanol and the efficient catalytic effect of platinum catalyst ensure the uniform formation and stability of the silicone rubber network structure, thereby maintaining performance in extremely high temperature environments.

[0086] In one implementation according to the present application, Figure 4 As shown, one or more pressure sensors 4 are embedded in the heat-resistant buffer material layer 13, and the pressure sensor 4 is led to the ear end of the negative electrode through a wire to monitor the pressure of each area of ​​the negative electrode in real time. By embedding the pressure sensor 4 in the heat-resistant buffer material layer 13, real-time monitoring and mapping of the pressure distribution in different areas of the negative electrode can be achieved, and local stress anomalies can be discovered and located in time, providing data support for battery safety protection and fault diagnosis, greatly improving the intelligence level and reliability of the battery management system.

[0087] In one implementation according to the present application, Figure 5 As shown, a first temperature control material layer 16 is further arranged between the first copper foil layer 11 and the heat-resistant buffer material layer 13, and a second temperature control material layer 17 is further arranged between the second copper foil layer 12 and the heat-resistant buffer material layer 13; the shapes of the first temperature control material layer 16 and the second temperature control material layer 17 are both adapted to the shape of the surface of the trapezoidal protrusion 14 of the heat-resistant buffer material layer 13; the phase change temperatures of the first temperature control material layer 16 and the second temperature control material layer 17 are both 57~62°C.

[0088] In one implementation of the present application, the first temperature control material layer 16 and the second temperature control material layer 17 both include the following compositions in weight proportions: 45-55 parts of octadecanoic acid glycerol, 20-25 parts of palmitic acid, 10-15 parts of polyethylene glycol 4000, 3-5 parts of carbon nanotubes, 2-3 parts of boron nitride nanosheets, 1-2 parts of expanded graphite, and 0.5-1 parts of nano-magnesium oxide.

[0089] Among them, octadecanoic acid glycerol and palmitic acid are the main phase change materials, providing high-temperature phase change capability, and the mixed use can adjust the phase change temperature range; polyethylene glycol 4000 adjusts the phase change temperature, increases the heat capacity of the material, and improves the heat storage capacity; carbon nanotubes significantly improve the thermal conductivity of the material and improve the rapid distribution of heat in the phase change material; boron nitride nanosheets further enhance heat conduction and improve the thermal stability of the material; expanded graphite increases the specific surface area of ​​the material, improves the heat exchange efficiency, and improves the thermal conductivity and flame retardancy of the material; nano-magnesium oxide enhances the thermal stability and flame retardancy of the material and improves the structural integrity of the material at high temperatures. The phase change temperature of the temperature control material layer is 57℃~62℃. When it reaches the phase change temperature, it can quickly absorb heat, effectively adjust the battery temperature, and improve the heat and high temperature resistance of the battery.

[0090] In one implementation of the present application, the preparation method of the first temperature control material layer 16 or the second temperature control material layer 17 is as follows:

[0091] (1) Stearyl octadecanoate and palmitic acid are mixed according to a ratio, heated to melt in an oil bath at 85-95° C., and stirred evenly;

[0092] (2) adding polyethylene glycol 4000 to the molten mixture of step (1) and continuing to stir until it is completely dissolved;

[0093] (3) dispersing carbon nanotubes and boron nitride nanosheets in N-methylpyrrolidone and ultrasonically treating for 30 minutes;

[0094] (4) slowly adding the suspension of step (3) into the molten mixture of step (2), and stirring at high speed for 45 minutes;

[0095] (5) adding expanded graphite and nano magnesium oxide, and continuing high-speed stirring for 20 minutes to obtain a temperature control material layer slurry;

[0096] (6) The temperature control material layer slurry is sprayed onto the outer surface of the heat-resistant buffer material layer 13 and dried to obtain a first temperature control material layer 16 or a second temperature control material layer 17 of a desired shape and thickness.

[0097] In one implementation according to the present application, Figure 6As shown, a first modified thermally conductive silicone 18 is further arranged between the first copper foil layer 11 and the heat-resistant buffer material layer 13, and a second modified thermally conductive silicone 19 is further arranged between the second copper foil layer 12 and the heat-resistant buffer material layer 13; the shapes of the first modified thermally conductive silicone 18 and the second modified thermally conductive silicone 19 are both adapted to the shape of the surface of the trapezoidal protrusion 14 of the heat-resistant buffer material layer 13; the porosity of the first modified thermally conductive silicone 18 and the second modified thermally conductive silicone 19 are both 65%~85%; the first copper foil layer 11 and the heat-resistant buffer material layer 13 are bonded and connected by the first modified thermally conductive silicone 18; the second copper foil layer 12 and the heat-resistant buffer material layer 13 are bonded and connected by the second modified thermally conductive silicone 19.

[0098] A modified thermally conductive silicone with a porosity of 65% to 85% is embedded between the first copper foil layer 11, the second copper foil layer 12 and the heat-resistant buffer material layer 13, which not only has good thermal conductivity, but also has a good energy absorption and buffering effect, further preventing stress concentration from causing deformation, fracture or damage of the composite current collector 1, thereby significantly improving the mechanical stability and reliability of the battery; in addition, the modified thermally conductive silicone can also bond and fix the first copper foil layer 11, the second copper foil layer 12 and the heat-resistant buffer material layer 13, and its thermal conductivity can reach 6-10W / (m·k), which can accelerate the heat conduction and dissipation of the battery at high temperature and avoid local overheating.

[0099] The preparation method of the modified thermally conductive silica gel is as follows:

[0100] 1) Boron nitride and KH570 silane coupling agent were dispersed in 100 ml of aqueous solution at a mass ratio of 10:1, with concentrations of 40 mg / ml and 4 mg / ml, respectively. The mixed dispersion was placed in a water bath ultrasound at 0°C for 40 minutes, then centrifuged to remove excess solvent, and lyophilized to obtain modified boron nitride powder.

[0101] 2) The modified boron nitride powder and graphene were dispersed in a mixed solvent of alcohol and water in a mass ratio of 1:5, with concentrations of 1.2 mg / ml and 6 mg / ml, respectively. 2 mg / ml carbon nanotubes were added at the same time, and ultrasonic cell crusher was used for 10 min at a power of 1200 W to obtain graphene slurry.

[0102] 3) The polyurethane sponge foam was immersed in a 2 mol / L NaOH solution, treated in 40°C warm water for 3.5 h, and then placed in a 5 mg / ml anilinemethyltriethoxysilane aqueous solution and immersed for 24 h to obtain a modified polyurethane porous foam.

[0103] 4) The modified polyurethane porous foam structure was immersed in the uniform graphene slurry prepared above, and ultrasonicated in a water bath for 20 minutes at 0°C. It was dried at 60°C, and then heated from 60°C to 200°C at a heating rate of 15°C per minute, and then heated from 200°C to 380°C at a heating rate of 3°C per minute for 30 minutes, and the porous material was removed to obtain a three-dimensional porous graphene-boron nitride composite material.

[0104] 5) The three-dimensional porous graphene-boron nitride composite material obtained above is immersed in silica gel (Wacker SEMICOSIL9212), and the bubbles are removed by vacuuming. The composite material is sprayed on the outer surface of the heat-resistant buffer material layer 13, and placed in an oven at 120° C. for curing for 15 minutes to obtain a modified thermally conductive silica gel.

[0105] In addition, the present invention also provides a method for preparing a negative electrode of a lithium ion battery with a long cycle life and high initial efficiency, comprising the following steps:

[0106] 1) Preparation of composite current collector 1:

[0107] a) preparing a ceramic silicone foam rubber material according to the above-mentioned method for preparing the ceramic silicone foam;

[0108] b) vulcanizing and foaming the ceramic silicone foam rubber material through a molding process to obtain a heat-resistant buffer material layer 13 having trapezoidal protrusions 14 on both sides of the surface;

[0109] c) spraying a copper foil layer of the same thickness on the surface of the heat-resistant buffer material layer 13 by magnetron sputtering, and drying the copper foil layer to obtain a composite current collector 1;

[0110] 2) Preparation of silicon-carbon negative electrode active material coating 2:

[0111] d) mixing the silicon-carbon material, the conductive agent and the binder in a mass ratio of (80-99.5):(0.2-10):(0.3-10) in deionized water to make the solid content 60-70%, and stirring evenly to obtain a silicon-carbon negative electrode active material coating 2 slurry;

[0112] e) coating the negative electrode active material coating 2 slurry on at least one surface of the composite current collector 1 and drying the slurry to obtain the silicon-carbon negative electrode active material coating 2;

[0113] 3) Preparation of lithium supplement coating 3:

[0114] f) mixing an inorganic lithium-containing compound, halloysite nanotube powder and lithium polyacrylate in a mass ratio of (20-25):(65-75):(2-5) in deionized water to make a solid content of 50-60%, thereby obtaining a lithium supplement coating 3 slurry;

[0115] g) coating the lithium supplement coating 3 slurry on the outer surface of the silicon-carbon negative electrode active material coating 2 and drying the coating to obtain a lithium ion battery negative electrode containing the lithium supplement coating 3.

[0116] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. The reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained commercially.

[0117] Example 1

[0118] Preparation of negative electrode sheet:

[0119] The lithium-ion battery negative electrode provided in this embodiment includes a composite current collector 1, a silicon-carbon negative electrode active material coating 2 coated on a surface of the composite current collector 1, and a lithium supplement coating 3 coated on the outer surface of the silicon-carbon negative electrode active material coating 2; the lithium supplement coating 3 includes an inorganic lithium-containing compound, halloysite nanotube powder and lithium polyacrylate, and the mass ratio of the inorganic lithium-containing compound, halloysite nanotube powder and lithium polyacrylate is 25:70:5; the inorganic lithium-containing compound is combined into a mixture of lithium borate and lithium carbonate in a mass ratio of 1:1.

[0120] The average particle size R1 of the inorganic lithium-containing compound is 15 μm, the average particle size R2 of the halloysite nanotube powder is 5 μm; and the thickness of the lithium-replenishing coating 3 is 3 μm.

[0121] Among them, the silicon-carbon negative electrode active material coating 2 includes silicon-carbon material, a conductive agent and a binder, and the mass ratio of the silicon-carbon material, the conductive agent and the binder is 95:2:3; the silicon-carbon material is a mixture of silicon oxide and hard carbon in a mass ratio of 1:2, the conductive agent is carbon nanotubes, and the binder is styrene-butadiene rubber.

[0122] Among them, the composite current collector 1 includes a first copper foil layer 11, a second copper foil layer 12 and a heat-resistant buffer material layer 13 arranged between the first copper foil layer 11 and the second copper foil layer 12; a plurality of trapezoidal protrusions 14 are arranged on both side surfaces of the heat-resistant buffer material layer 13, and the first copper foil layer 11 and the second copper foil layer 12 are both provided with a plurality of trapezoidal grooves 15 embedded with the trapezoidal protrusions 14, the cross-sectional width of the trapezoidal protrusions 14 gradually increases from the inside to the outside, and the cross-sectional width of the trapezoidal grooves 15 gradually decreases from the inside to the outside, and an interlocking structure is formed between the first copper foil layer 11 and the second copper foil layer 12 through the cooperation of the trapezoidal protrusions 14 and the trapezoidal grooves 15.

[0123] Among them, the heat-resistant buffer material layer 13 is ceramic silicone foam, and the ceramic silicone foam includes the following components in weight proportion: 35 parts of vinyl silicone oil, 15 parts of white carbon black, 30 parts of nano-ceramic powder, 0.5 parts of ethynyl cyclohexanol, 5 parts of hydrogenated silicone oil, 5 parts of hydroxyl silicone oil, 0.5 parts of platinum catalyst, 15 parts of β-eucryptite, and 4 parts of halloysite nanotubes.

[0124] Among them, the height of the trapezoidal protrusion 14 is g, the depth of the trapezoidal groove 15 is h, the cross-sectional width of the trapezoidal protrusion 14 is w, the cross-sectional width of the trapezoidal groove 15 is d, the thickness of the heat-resistant buffer material layer 13 is G, and the thickness of the first copper foil layer 11 and the second copper foil layer 12 are both H, wherein g, h, w, d, G and H satisfy the relationship: g=h, w=d, 0.1G≤g≤0.3G, 0.2H≤h≤0.4H, H<G; the sum of the forward projection areas of all the trapezoidal protrusions 14 on the surface of one side of the heat-resistant buffer material layer 13 is S1, and the forward projection area of ​​the heat-resistant buffer material layer 13 is S; wherein S1 and S satisfy the relationship: 0.5S≤S1≤0.7S.

[0125] Specifically, in this embodiment, the height g of the trapezoidal protrusion 14 is 3μm, the depth h of the trapezoidal groove 15 is 3μm, the cross-sectional width of the trapezoidal protrusion 14 is 100μm on the short side and 300μm on the long side, the cross-sectional width of the trapezoidal groove 15 is 100μm on the short side and 300μm on the long side, the thickness G of the heat-resistant buffer material layer 13 is 15μm, the thickness H of the first copper foil layer 11 and the second copper foil layer 12 are both 10μm; and S1 / S=0.6.

[0126] The preparation method of the negative electrode sheet is as follows:

[0127] 1) Preparation of composite current collector 1:

[0128] a) preparing a ceramic silicone foam rubber material according to the above-mentioned method for preparing the ceramic silicone foam;

[0129] b) vulcanizing and foaming the ceramic silicone foam rubber material through a molding process to obtain a heat-resistant buffer material layer 13 having trapezoidal protrusions 14 on both sides of the surface;

[0130] c) spraying a copper foil layer of the same thickness on the surface of the heat-resistant buffer material layer 13 by magnetron sputtering, and drying the copper foil layer to obtain a composite current collector 1;

[0131] 2) Preparation of silicon-carbon negative electrode active material coating 2:

[0132] d) mixing the silicon-carbon material, the conductive agent and the binder in deionized water at a mass ratio of 95:2:3 to make a solid content of 60%, and stirring evenly to obtain a silicon-carbon negative electrode active material coating 2 slurry;

[0133] e) coating the negative electrode active material coating 2 slurry on one surface of the composite current collector 1 and drying the slurry to obtain the silicon-carbon negative electrode active material coating 2;

[0134] 3) Preparation of lithium supplement coating 3:

[0135] f) mixing an inorganic lithium-containing compound, halloysite nanotube powder and lithium polyacrylate in a mass ratio of 25:70:5 in deionized water to make a solid content of 50%, and stirring evenly to obtain a lithium supplement coating 3 slurry;

[0136] g) coating the lithium supplement coating 3 slurry on the outer surface of the silicon-carbon negative electrode active material coating 2 and drying the coating to obtain a negative electrode sheet containing the lithium supplement coating 3 .

[0137] Preparation of positive electrode:

[0138] The positive electrode active material lithium nickel cobalt manganese oxide, the conductive agent conductive carbon black, and the binder polyvinylidene fluoride are dispersed in the solvent NMP (N-methylpyrrolidone) in a mass ratio of 95:2:3 to form a uniform slurry, the slurry is evenly coated on the surface of the current collector aluminum foil, and then transferred to a vacuum drying oven for complete drying to obtain a positive electrode sheet.

[0139] Preparation of electrolyte:

[0140] Ethylene carbonate (EC) and diethyl carbonate (DEC) are mixed at a volume ratio of 1:1, and then FEC (fluoroethylene carbonate) is added at a volume percentage of 5%. Then, the fully dried lithium salt LiPF6 is dissolved in a mixed organic solvent at a concentration ratio of 1 mol / L to prepare an electrolyte.

[0141] Preparation of isolation film: A PET / PP composite film with a thickness of 12 microns was selected.

[0142] Preparation of lithium-ion batteries:

[0143] The negative electrode sheet, separator, and positive electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and the electrolyte is added, and a lithium-ion battery is assembled according to conventional processes.

[0144] Example 2

[0145] Different from Example 1, the lithium-replenishing coating 3 of the negative electrode of this embodiment further includes 2 parts by weight of an amine-based stabilizer, which is BASF Tinuvin 770.

[0146] The rest is the same as in Example 1 and will not be described again here.

[0147] Example 3

[0148] Different from Example 1, a first temperature control material layer 16 is further arranged between the first copper foil layer 11 and the heat-resistant buffer material layer 13 in the composite current collector 1 of the negative electrode of this embodiment, and a second temperature control material layer 17 is further arranged between the second copper foil layer 12 and the heat-resistant buffer material layer 13; the shapes of the first temperature control material layer 16 and the second temperature control material layer 17 are both adapted to the shape of the surface of the trapezoidal protrusion 14 of the heat-resistant buffer material layer 13; the thickness of the first temperature control material layer 16 and the second temperature control material layer 17 are both 2μm; the phase change temperature of the first temperature control material layer 16 and the second temperature control material layer 17 are both 57~62℃.

[0149] The first temperature control material layer 16 and the second temperature control material layer 17 both include the following compositions in weight proportions: 50 parts of octadecyl glycerol, 22 parts of palmitic acid, 13 parts of polyethylene glycol 4000, 4 parts of carbon nanotubes, 2 parts of boron nitride nanosheets, 1 part of expanded graphite, and 1 part of nano magnesium oxide.

[0150] The preparation method of the first temperature control material layer 16 or the second temperature control material layer 17 is as follows:

[0151] (1) Stearyl glycerol and palmitic acid are mixed according to a ratio, heated to melt in an oil bath at 85-95° C., and stirred evenly;

[0152] (2) adding polyethylene glycol 4000 to the molten mixture of step (1) and continuing to stir until it is completely dissolved;

[0153] (3) dispersing carbon nanotubes and boron nitride nanosheets in N-methylpyrrolidone and ultrasonically treating for 30 minutes;

[0154] (4) slowly adding the suspension of step (3) into the molten mixture of step (2), and stirring at high speed for 45 minutes;

[0155] (5) adding expanded graphite and nano magnesium oxide, and continuing high-speed stirring for 20 minutes to obtain a temperature control material layer slurry;

[0156] (6) The temperature control material layer slurry is sprayed onto the outer surface of the heat-resistant buffer material layer 13 and dried to obtain a first temperature control material layer 16 or a second temperature control material layer 17 of a desired shape and thickness.

[0157] The rest is the same as in Example 1 and will not be described again here.

[0158] Example 4

[0159] Different from Example 1, in the composite current collector 1 of the negative electrode of this embodiment, a first modified thermally conductive silicone 18 is further arranged between the first copper foil layer 11 and the heat-resistant buffer material layer 13, and a second modified thermally conductive silicone 19 is further arranged between the second copper foil layer 12 and the heat-resistant buffer material layer 13; the shapes of the first modified thermally conductive silicone 18 and the second modified thermally conductive silicone 19 are both adapted to the shape of the surface of the trapezoidal protrusion 14 of the heat-resistant buffer material layer 13; the thickness of the first modified thermally conductive silicone 18 and the second modified thermally conductive silicone 19 are both 2μm; the porosity of the first modified thermally conductive silicone 18 and the second modified thermally conductive silicone 19 are both 75%; the first copper foil layer 11 and the heat-resistant buffer material layer 13 are bonded and connected by the first modified thermally conductive silicone 18; the second copper foil layer 12 and the heat-resistant buffer material layer 13 are bonded and connected by the second modified thermally conductive silicone 19.

[0160] The preparation method of the modified thermally conductive silica gel is as follows:

[0161] 1) Boron nitride and KH570 silane coupling agent were dispersed in 100 ml of aqueous solution at a mass ratio of 10:1, with concentrations of 40 mg / ml and 4 mg / ml, respectively. The mixed dispersion was placed in a water bath ultrasound at 0°C for 40 minutes, then centrifuged to remove excess solvent, and lyophilized to obtain modified boron nitride powder.

[0162] 2) The modified boron nitride powder and graphene were dispersed in a mixed solvent of alcohol and water in a mass ratio of 1:5, with concentrations of 1.2 mg / ml and 6 mg / ml, respectively. 2 mg / ml carbon nanotubes were added at the same time, and ultrasonic cell crusher was used for 10 min at a power of 1200 W to obtain graphene slurry.

[0163] 3) The polyurethane sponge foam was immersed in a 2 mol / L NaOH solution, treated in 40°C warm water for 3.5 h, and then placed in a 5 mg / ml anilinemethyltriethoxysilane aqueous solution and immersed for 24 h to obtain a modified polyurethane porous foam.

[0164] 4) The modified polyurethane porous foam structure was immersed in the uniform graphene slurry prepared above, and ultrasonicated in a water bath for 20 minutes at 0°C. It was dried at 60°C, and then heated from 60°C to 200°C at a heating rate of 15°C per minute, and then heated from 200°C to 380°C at a heating rate of 3°C per minute for 30 minutes, and the porous material was removed to obtain a three-dimensional porous graphene-boron nitride composite material.

[0165] 5) The three-dimensional porous graphene-boron nitride composite material obtained above is immersed in silica gel (Wacker SEMICOSIL9212), and the bubbles are removed by vacuuming. The composite material is sprayed on the outer surface of the heat-resistant buffer material layer 13, and placed in an oven at 120° C. for curing for 15 minutes to obtain a modified thermally conductive silica gel.

[0166] The rest is the same as in Example 1 and will not be described again here.

[0167] Comparative Example 1

[0168] Different from Example 1, the outer surface of the silicon-carbon negative electrode active material coating 2 of the negative electrode of this comparative example is not coated with a lithium supplement coating 3 .

[0169] The rest is the same as in Example 1 and will not be described again here.

[0170] Comparative Example 2

[0171] Different from Example 1, the inorganic lithium-containing compound of the lithium-supplementing coating 3 of the negative electrode of this comparative example is only lithium carbonate.

[0172] The rest is the same as in Example 1 and will not be described again here.

[0173] Comparative Example 3

[0174] Different from Example 1, the composite current collector 1 of the negative electrode of this comparative example adopts a three-layer composite current collector of copper foil-PET-copper foil.

[0175] The rest is the same as in Example 1 and will not be described again here.

[0176] The mechanical and electrochemical performance tests were performed on the negative electrode sheets and lithium-ion batteries of the above-mentioned embodiments and comparative examples, respectively. The test results are shown in Table 1.

[0177] 1) Disassembly and lithium analysis test: After the battery is pre-charged in the formation stage, fully charge and disassemble to observe its interface.

[0178] 2) Ductility test: Under the same pressure (20 tons), the negative electrode sheets prepared in the embodiment and the comparative example were rolled to observe whether there was brittle fracture or cracking on the surface of the electrode sheets. If any of the above phenomena occurred, it means that the ductility is poor.

[0179] 3) High temperature cycle test: The cycle capacity retention rate (%) of the above lithium-ion battery during 300 charge and discharge cycles at high temperature (55°C) is tested at a charge and discharge voltage of 2.5V to 3.65V and a charge and discharge rate of 1C / 1C. That is, the discharge capacity of the lithium-ion battery in the first cycle at the corresponding temperature is set to 1, and the ratio of the discharge capacity during continuous charge and discharge cycles under the same conditions to the discharge capacity of the first cycle is the capacity retention rate (%) under the number of cycles.

[0180] Table 1

[0181] It can be seen from the test results in Table 1 that the negative electrode prepared by the present invention has good ductility and structural stability, can effectively prevent the negative electrode from brittle fracture or cracking, and can absorb the negative electrode expansion force, reduce the volume change of the negative electrode material, maintain the relative stability of the negative electrode structure, and inhibit the generation of negative electrode lithium dendrites. The lithium ion battery prepared using the negative electrode of the present invention has a higher first efficiency and a longer cycle life.

[0182] By comparing Example 1 with Comparative Example 1, it can be seen that coating the lithium supplement coating on the outer surface of the silicon-carbon negative electrode active material coating of the negative electrode in the present invention can effectively improve the initial efficiency and cycle life of the battery.

[0183] By comparing Example 1 and Comparative Example 2, it can be seen that compared with a single lithium-containing compound (lithium carbonate), the mixture of lithium borate and lithium carbonate used in the present invention as the inorganic lithium-containing compound has better first effect and cycle performance, indicating that the use of a mixture of lithium borate and lithium carbonate as an inorganic lithium-containing compound can give play to the synergistic effect of the two, provide efficient and reversible lithium compensation, improve the first coulombic efficiency and cycle stability of the silicon-carbon negative electrode, and take into account the lithium ion transfer kinetics, interface compatibility and safety performance.

[0184] By comparing Example 1 and Comparative Example 3, it can be seen that compared with the negative electrode using the copper foil-PET-copper foil current collector, the negative electrode using the composite current collector with the special structure of the present invention has better ductility and structural stability, can effectively prevent the negative electrode from brittle fracture or cracking, and can absorb the negative electrode expansion force, reduce the volume change of the negative electrode material, maintain the relative stability of the negative electrode structure, and inhibit the generation of negative electrode lithium dendrites.

[0185] By comparing Example 1 and Example 2, it can be seen that when an amine stabilizer is further added to the lithium replenishing coating of the negative electrode, the initial efficiency and cycle performance of the battery can be further improved. This is because the amine functional group of the amine stabilizer can react with the inorganic lithium-containing compound and the oxygen free radicals released during the delithiation process of the positive electrode active material, thereby blocking the damage of the oxygen free radicals to the electrolyte solvent and effectively improving the cycle performance of the battery.

[0186] By comparing Example 1 and Example 3, it can be seen that when a temperature control material layer is further provided inside the composite current collector of the negative electrode, the heat resistance and high temperature resistance of the battery can be further improved, indicating that the temperature control material layer can accelerate the heat conduction and dissipation of the battery at high temperature, avoid local overheating, and thus improve the high temperature cycle performance of the battery.

[0187] By comparing Example 1 and Example 4, it can be seen that when modified thermally conductive silicone is further provided inside the composite current collector of the negative electrode, it helps to further improve the high-temperature cycle performance of the battery, which means that the modified thermally conductive silicone not only has a good energy absorption and buffering effect, but can also adjust the stress uniformly distributed on the surface of the pole piece, and can accelerate heat dispersion, thereby improving the high-temperature resistance of the battery.

[0188] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0189] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A negative electrode for a lithium-ion battery with a long cycle life and high initial efficiency, characterized in that: It comprises a composite current collector, a silicon-carbon negative electrode active material coating coated on at least one surface of the composite current collector, and a lithium supplement coating coated on the outer surface of the silicon-carbon negative electrode active material coating; the lithium supplement coating comprises an inorganic lithium-containing compound, halloysite nanotube powder and lithium polyacrylate, and the mass fraction ratio of the inorganic lithium-containing compound, the halloysite nanotube powder and the lithium polyacrylate is (20-25): (65-75): (2-5); the inorganic lithium-containing compound is a mixture of lithium borate and lithium carbonate in a mass ratio of (1-2):

1.

2. The negative electrode for a lithium-ion battery with a long cycle life and high initial efficiency according to claim 1, characterized in that: The particle size of the inorganic lithium-containing compound is R1, and the particle size of the halloysite nanotube powder is R2, wherein R1 and R2 satisfy the relationship: 2≤R1 / R2≤5.

3. The negative electrode for a lithium-ion battery with a long cycle life and high initial efficiency according to claim 2, characterized in that: The particle size R1 of the inorganic lithium-containing compound is 2-50 μm, and the particle size R2 of the halloysite nanotube powder is 1-10 μm.

4. The negative electrode for a lithium-ion battery with a long cycle life and high initial efficiency according to claim 1, characterized in that: The silicon-carbon negative electrode active material coating includes a silicon-carbon material, a conductive agent and a binder, and the mass ratio of the silicon-carbon material, the conductive agent and the binder is (80~99.5):(0.2~10):(0.3~10); the silicon-carbon material is a mixture of silicon oxide and hard carbon in a mass ratio of 1:(1~2), the conductive agent is at least one of carbon nanofibers, carbon nanotubes and graphene, and the binder is at least one of lithium polyacrylate, ethylene oxide, nitrile rubber, styrene-butadiene rubber and polyvinyl alcohol.

5. The negative electrode for a lithium-ion battery with a long cycle life and high initial efficiency according to claim 1, characterized in that: The composite current collector includes a first copper foil layer, a second copper foil layer, and a heat-resistant buffer material layer arranged between the first copper foil layer and the second copper foil layer; a plurality of trapezoidal protrusions are arranged on both side surfaces of the heat-resistant buffer material layer, and the first copper foil layer and the second copper foil layer are both provided with a plurality of trapezoidal grooves embedded with the trapezoidal protrusions, the cross-sectional width of the trapezoidal protrusions gradually increases from the inside to the outside, and the cross-sectional width of the trapezoidal grooves gradually decreases from the inside to the outside, and an interlocking structure is formed between the first copper foil layer and the second copper foil layer through the cooperation of the trapezoidal protrusions and the trapezoidal grooves.

6. The negative electrode for a lithium-ion battery with a long cycle life and high initial efficiency according to claim 5, characterized in that: The heat-resistant buffer material layer is a ceramic silicone foam, which includes the following components in weight proportion: 30-40 parts of vinyl silicone oil, 10-20 parts of white carbon black, 20-50 parts of nano-ceramic powder, 0.1-1.0 parts of ethynyl cyclohexanol, 1-10 parts of hydrogen-containing silicone oil, 1-10 parts of hydroxy silicone oil, 0.1-1.0 parts of platinum catalyst, 10-20 parts of β-eucryptite, and 1-8 parts of halloysite nanotubes.

7. The negative electrode for a lithium-ion battery with a long cycle life and high initial efficiency according to claim 5, characterized in that: The height of the trapezoidal protrusion is g, the depth of the trapezoidal groove is h, the cross-sectional width of the trapezoidal protrusion is w, the cross-sectional width of the trapezoidal groove is d, the thickness of the heat-resistant buffer material layer is G, and the thickness of the first copper foil layer and the second copper foil layer are both H, wherein g, h, w, d, G and H satisfy the relationship: g=h, w=d, 0.1G≤g≤0.3G, 0.2H≤h≤0.4H, H<G.

8. The negative electrode for a lithium-ion battery with a long cycle life and high initial efficiency according to claim 5 or 7, characterized in that: The sum of the forward projection areas of all the trapezoidal protrusions on the surface of one side of the heat-resistant buffer material layer is S1, and the forward projection area of ​​the heat-resistant buffer material layer is S; wherein S1 and S satisfy the relationship: 0.5S≤S1≤0.7S.

9. The negative electrode for a lithium-ion battery with a long cycle life and high initial efficiency according to claim 6, characterized in that: The preparation method of the ceramic silicone foam is as follows: Step S1, adding vinyl silicone oil, white carbon black, nano ceramic powder and β-eucryptite into a kneader, kneading into a mass at 130-150° C., cooling, and obtaining a base rubber; Step S2, stirring and mixing the hydroxy silicone oil and the halloysite nanotubes to obtain a foaming mixture; wherein the stirring and mixing speed is 23000-26000 r / min, and the mixing time is 10-25 s; Step S3, adding the foaming mixture, ethynyl cyclohexanol, hydrogen-containing silicone oil, and platinum catalyst into the base rubber, mixing evenly, to obtain a rubber material; Step S4, vulcanizing and foaming the rubber material by a molding process to obtain the ceramicized silicone foam.

10. A method for preparing a negative electrode for a lithium-ion battery with a long cycle life and high initial efficiency according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) Composite current collector production: a) preparing a ceramic silicone foam compound according to the method for preparing the ceramic silicone foam according to claim 9; b) vulcanizing and foaming the ceramic silicone foam rubber material through a molding process to obtain a heat-resistant buffer material layer having trapezoidal protrusions on both sides of the surface; c) spraying a copper foil layer of the same thickness on the surface of the heat-resistant buffer material layer by magnetron sputtering, and drying the copper foil layer to obtain a composite current collector; 2) Preparation of silicon-carbon negative electrode active material coating: d) mixing the silicon-carbon material, the conductive agent and the binder in a mass ratio of (80-99.5):(0.2-10):(0.3-10) in deionized water, and stirring evenly to obtain a silicon-carbon negative electrode active material coating slurry; e) coating the negative electrode active material coating slurry on at least one surface of the composite current collector and drying it to obtain a silicon-carbon negative electrode active material coating; 3) Preparation of lithium supplement coating: f) mixing an inorganic lithium-containing compound, halloysite nanotube powder and lithium polyacrylate in a mass ratio of (20-25):(65-75):(2-5) in deionized water to make a solid content of 50-60%, thereby obtaining a lithium supplement coating slurry; g) coating the lithium supplement coating slurry on the outer surface of the silicon-carbon negative electrode active material coating and drying the coating to obtain a lithium ion battery negative electrode containing the lithium supplement coating.